Gospodarka finansowa miasta. Wybrane zagadnienia - Nieplowicz, Maria (The Financial Economy of the City, 2006)
The article presents the basis of cities' existence in comparison with other territorial self--governmental bodies. The following section concerns the rudiments of the city's financial economy as well as the essence of the budget procedures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 281-286